2017
DOI: 10.1016/j.apsusc.2016.05.177
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Ni@CoO core-shell nanoparticle films synthesized by sequential layer deposition

Abstract: Films of Ni@CoO core-shell nanoparticles (NP Ni core size d ≈ 11 nm) have been grown on Si/SiOx and lacey carbon supports, by a sequential layer deposition method: a first layer of CoO was evaporated on the substrate, followed by the deposition of a layer of pre-formed, mass-selected Ni NPs, and finally an overlayer of CoO was added. The Ni NPs were formed by a magnetron gas aggregation source, and mass selected with a quadrupole mass filter. The morphology of the films was investigated with Scanning Electron … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 36 publications
1
7
0
Order By: Relevance
“…The data also showed that NiO was formed during the deposition of the CoO overlayer. Oxidation of the external layers of the Ni cores, as previously reported [20,21], can be ascribed to a slightly higher Table I together with the corresponding nominal thickness of the CoO overlayer, t 3 CoO . It must be stressed that t 3 CoO is a quantity expressing the amount of CoO deposited during step 3 of the NP growth method summarized in the previous section (growth of the third layer) and estimated by the evaporation rate measured by the quartz microbalance, while t CoO is an estimate of the CoO shell average thickness in Ni@NiO@CoO NPs as obtained by analysis of the XPS Co 2p components [38].…”
Section: Morphology and Structuresupporting
confidence: 71%
See 3 more Smart Citations
“…The data also showed that NiO was formed during the deposition of the CoO overlayer. Oxidation of the external layers of the Ni cores, as previously reported [20,21], can be ascribed to a slightly higher Table I together with the corresponding nominal thickness of the CoO overlayer, t 3 CoO . It must be stressed that t 3 CoO is a quantity expressing the amount of CoO deposited during step 3 of the NP growth method summarized in the previous section (growth of the third layer) and estimated by the evaporation rate measured by the quartz microbalance, while t CoO is an estimate of the CoO shell average thickness in Ni@NiO@CoO NPs as obtained by analysis of the XPS Co 2p components [38].…”
Section: Morphology and Structuresupporting
confidence: 71%
“…3) of the sequential deposition, with the morphology of a percolated film. SEM images of Ni@NiO@CoO NPs grown on Si/SiO x have been previously reported [20]; at increasing coverage of the CoO overlayer, the islands cover completely the Ni NP cores and extend over neighboring NPs, forming nanostructures of cubic shape with size between 15 and 50 nm at the highest overlayer thickness studied (t 3 CoO = 6 nm). XPS analysis confirmed that the oxide shell consisted mainly of CoO (at variance with previous experiments [21], where the NPs prepared with a similar technique had an oxide shell composed of Co 3 O 4 and Co suboxides) and showed also that an interfacial NiO shell was formed during the deposition of the CoO overlayer.…”
Section: Morphology and Structurementioning
confidence: 58%
See 2 more Smart Citations
“…Since the electronegativity values of Ni and Co (1.88 Pauling) are very close, it is reasonable to deduce that formation of NiO can take place, as well as oxidized Co. XMCD data taken at remanence from Ni@CoO NP films synthesized with sequential layer deposition revealed the existence of a dichroic signal at room temperature, a possible indication of stabilization of the Ni NP cores in a FM phase [91].…”
Section: Magnetic Properties Of Metal@oxide Np: Exchange Biasmentioning
confidence: 99%